The proliferance of BIM adoption amongst clients for the minimization of variance orders relevant to the South African building industry - Weitz, Christian Matthys (My University, 2016)
The adoption rate of BIM (Building information Modelling) in South Africa is substantially lower than many other countries both developed and developing, which is surprising given BIM’s significant advantages particularly in automating clash detection within design information, which has been a significant challenge for designers and project managers. Such clashes between inter alia different building services and systems are frequently a major cause of cost overruns and delays on South African construction projects. The benefits of such BIM functionality may well be the necessary driving force behind BIM adoption. However, in adopting change, the industry is often slow and often requires clients and end users to drive change in a fragmented industry as they are often the parties that stands to benefit the most, and this is arguably true of BIM. This study focuses on private sector clients of the South African construction industry, and whether they have identified the potential of using BIM to minimise clashes between building services on their projects. The study reviewed literature on the current state of BIM adoption internationally and in South Africa along with the benefits of using BIM on projects in South Africa and abroad. The benefits of BIM adoption were summarised and were distributed to several pre-selected interviewees to read. Interviews were conducted based on a questionnaire that was set up drawn from client organisations in the private sector. The data was represented graphically and the outcomes of the interviews analysed. The interviewees were generally of the mind that they should not be the driving force behind BIM adoption. They all agreed that their consultants should implement any cost or time saving technology as a value added service to them. Keywords: BIM, Building Information Modelling, Clashes, Clash Detection, Property developers, Designers, Developers, Variations,
A research proposal submitted to the School of Construction Economics and Management, University of the Witswatersrand, in partial fulfilment of the requirements for a Master of Science in Building (Project management), 2016.
Keywords: Construction industry--South Africa; Project management--South Africa